Pengaruh Kadar Air Dan Porositas Tanah Terhadap Efisiensi Pemberian Pupuk Pada Tanaman Jagung - Laia, Murnimawati; Laia, Jupirinus (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This study aims to analyze the effect of soil moisture content and soil corrosiveness on fertilizer efficiency in maize crops. The method employed is an experimental approach with treatments of different soil moisture levels (low, medium, and high) and the measurement of soil corrosiveness. The results showed that optimal soil moisture positively contributes to plant growth, with higher average plant height and yields at high moisture levels compared to low moisture levels. Additionally, soils with low corrosiveness are better at retaining water and nutrients, thereby enhancing fertilizer uptake efficiency. The interaction between soil moisture and soil corrosiveness was found to significantly affect crop yields. This study concludes that effective management of soil moisture and corrosiveness can improve fertilizer efficiency, and it provides recommendations for farmers to adopt precise fertilization strategies for sustainable agriculture practices.